The Undying Controversy of the Presence of Slavs on the Island of Crete. Remarks on a New Book by Pantelis Haralampakis - Kaczyńska, Elwira; Witczak, Krzysztof Tomasz (Studia Ceranea, 2019)
The paper demonstrates the current state of research on the presence of Slavs on the island of Crete in the Middle Ages, as well as in the modern times. The basis for the discussion is a new book of Pantelis Haralampakis, published in 2016. There are numerous controversies surrounding the issues of the exact chronology of Slavic presence on the island, the lexical influence of South Slavic languages on the Cretan dialect of Modern Greek, as well as possible traces of Slavic settlements in the Cretan toponymy.